Quantitative evaluation of Zindagii Shoista (Living with Dignity) intervention to prevent violence against women in Tajikistan - Subhiya Mastonshoeva; Shahribonu Shonasimova; Parvina Gulyamova; Rachel Jewkes; Nwabisa Shai; Esnat Chirwa; Henri Myrttinen (Taylor & Francis Group, 2022)
Background Violence against women and girls (VAWG) is a major problem in Tajikistan, driven by conservative gender norms, the culturally ascribed position of young women, and poverty. Objective We evaluated Zindagii Shoista (Living with Dignity), an intervention developed with the aim of reducing VAWG through a combination of gender norm change, communication skills, and income-generating activities (IGA) over a period of 30 months. Methods The evaluation used a mixed-methods approach, combining quantitative and qualitative data collection. Eighty families from four villages were enrolled in the intervention and surveyed at baseline and on three subsequent occasions. From these families, 134 women and 102 men were interviewed at baseline, 153 women and 89 men 8 months later, 153 women and 93 men 15 months later, and 143 women and 82 men, 30 months after the baseline. Generalised random effects regression models were used to assess the trend in proportions or mean score over time. Results Over the 30 months, the proportion of women and men earning in the past month rose from 17.9% to 56.6% and 44.1% to 72%, respectively. Women and men's gender attitudes became significantly less patriarchal, and they reported less harmful gender norms in the community. Women and men reported less male controlling behaviour and greater woman involvement in decision-making. Women's reports of experience of emotional, physical, and sexual IPV significantly reduced. Depressive symptoms and suicidal thoughts reduced significantly for men and women, and self-rated health improved. Conclusions The quantitative findings are confirmed by the findings of the qualitative research and monitoring data. They demonstrate that Zindagii Shoista is a very promising intervention for strengthening gender relations, reducing IPV, and improving mental health and socio-economic circumstances for younger married women and their families in Tajikistan.